Reducing the Proportion of Single-source Procurement Management Application - Cui, Mingyan (Transactions on Economics, Business and Management Research, 2024)
Procurement plays a crucial role in modern enterprise management, where the level of procurement management has become a key component of the core competitive advantage for businesses. Enterprises need to tap into the third source of profit, which is the procurement cost of materials, and achieve the goal of increasing profits through procurement management and cost reduction. The article enumerates the reasons for the significant proportion of single-source procurement, emphasizing the theoretical basis and innovations introduced by the Materials Management Center. The establishment of a task force dedicated to addressing challenges in single-source procurement demonstrates the commitment to resolving issues in the procurement process. The article provides a detailed overview of the working methods employed by the Materials Management Center, with a special focus on compliance procurement. It describes the standardization of centralized review processes, overcoming difficulties associated with single-source procurement, and the implementation of annual plans and standardized specifications. Data reveals a consistent decline in the proportion of single-source procurement over the years, accompanied by a continuous increase in procurement efficiency and substantial savings in procurement funds.